The American Palm Cixiid, Haplaxius crudus - Brian Bahder (EDIS)
The American palm cixiid, Haplaxius crudus, is a common species of insect that belongs to the order Hemiptera, family Cixiidae.  It is widespread and abundant in the state of Florida, but also occurs as far north as South Carolina and as far west as Texas.  Furthermore, it is common throughout the Caribbean basin.  This insect feeds on a wide variety of palm species as adults while the immature stages feed on a wide variety of grass species.  This species is of high economic concern due to its ability to transmit the lethal yellowing (LY) phytoplasma (Howard and Thomas 1980) and is also the putative vector of lethal bronzing (LB) in Florida.